SURVEI PRAKTEK AKREDITASI LEMBAGA PENDIDIKAN KEJURUAN DAN TEKNOLOGI(VIET) DI NEGARA ANGGOTA ASEAN - Sukardi Sukardi (Jurnal Kependidikan, 2000)
Syney prqctice of WET accreditation in SHMEO member Countries lnd threb major objectives. These objectives were: l) to prwide information  -in ionnection with  accreditation; 2) tofacilitate information base -  WET instinition for developins other relevant research;  j)  to enhanbe the Center's'program in frnduc_ ting ap4lild rgsegrch in WET areas. The'sttidy Used survey approach in whlch  reiatgd data were gathered with research question as-gltide oJstudy. The questionnoive  center and  Jormal  -all  was developed-bi the docamentation was used to pather"  iffirmation. Before contributed to the respondenYts, the guestion_ naire was validated b1 using content  -vakdity.  A ndeded From the  survey praclice of WET Accreditation had frye findinps relate to institutional accreditation. These names of rutional accreditation body  findings'incfuded:  -sidy "firstlv.  NABI were udioi-i'fro* country tg cogilry. There were two typei of stntctural'NAB orggruzafion. Ihe. Notiotlal accreditation body consisted poveril- ment olJicer only, and the national accr6ditation boZv kat ?g iy:d !l-  g:!,1yment oficers, pnvate.persons, and coimunity leaders- Jecofidty, the national accreditation  bodies thot verv |mportant  position especially in maintainins the suolin of wfr institutions. Thirdly, ?rffi fistitutions In sevZral-ciitiet itii"a, received evaluation whereas. Their national accreditation 6oaii, did Not evatuate tty_g$"rs in soii  "oiiii.-'ri,iiinii'in, accreditation in the Wet institutions generitty ieri ii$'-l*ift getting: communifit" support, acceDtonce in proles$onor organimtio4 receiing  especially  for  federal fuads, acduirins non ,w,ff',i;#ii{;f i[!trlw:,i*,xpx;;"ytrf , 't![#f {ili,,i\i,Wffi pr?grqm gwde  if i,;:{,;i"ffi!";["f ;:!t:i:;; -tines; enlyqcing linkage betwden vocational scnoo$ anct tndustry; including new pblicy regardint imole_ y:T!!!?" of accrediianon:anfl iiprofiig-in; -frrji{"W'f;,industry.